Determination of Monthly Term Health Insurance Premiums for Individuals Based on Gender - Siahaan, Roy Donald Pangeran (Research Collaboration Community (RCC), 2025)
Health is one of the important aspects of human life, and protection against health risks is a necessity for every society. Health insurance is a solution in providing protection against financial risks from health. In its implementation, determining premiums is an important factor for insurance companies in order to cover claims from policyholders. Premiums are money paid by policyholders to insurance companies in order to receive benefits in the future. This study aims to determine the monthly premium for term health insurance which adjusted for each gender using actuarial approach. The premium is determined using the 2023 Indonesian Mortality Table and the Indonesian Morbidity Table I